VDIBA-based sinusoidal quadrature oscillator - Channumsin, Orapin; Tangsrirat, Worapong (My University, 2017)
An electronically tunable voltage-mode sinusoidal quadrature oscillator circuit, which is based on using the recently introduced active building block, namely voltage differencing inverting voltage buffered amplifier (VDIBA) has been presented. The presented quadrature oscillator uses two VDIBAs, one electronic grounded resistor, and two grounded passive capacitors, suitable for MOS-C realization. The circuit performs an single-element-controlled oscillator and provides the advantage features of independent electronic control of oscillation condition and oscillation frequency. The workability of the proposed circuit has been verified using PSPICE simulations based on VDIBA implemented in TSMC 0.25-µm CMOS technology, and the simulated results demonstrate a sufficient agreement with the theoretical conclusions.
Keywords: MOSFET-C realization; Quadrature oscillator; Voltage differencing inverting buffered amplifier (VDIBA); Voltage-mode circuits